2023
DOI: 10.2147/prom.s394247
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Quality of PROMs in Psychosocial Consequences of Colorectal Cancer Screening: A Systematic Review

Abstract: This systematic review aimed to assess the adequacy of measurement properties in Patient-Reported Outcome Measures (PROMs) used to quantify psychosocial consequences of colorectal cancer screening among adults at average risk. Methods: We searched four databases for eligible studies: MEDLINE, CINAHL, PsycINFO, and Embase. Our approach was inclusive and encompassed all empirical studies that quantified aspects of psychosocial consequences of colorectal cancer screening. We assessed the adequacy of PROM developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Future research could perform a more rigorous examination of the quality of questionnaire measures identified by the present review through application of the COSMIN Risk of Bias tool, as has been done in comparable and relevant research in the colorectal cancer screening field. 36 There is need to bring together experts (academic, public, patient, healthcare professional) in cancer screening harms, emotional processing, and scale measurement methodology to reach agreement on what to measure (outcomes) and how to measure it (outcome measures). 31 Existing relevant psychological theories could be utilised, such as those related to emotional response and processing (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could perform a more rigorous examination of the quality of questionnaire measures identified by the present review through application of the COSMIN Risk of Bias tool, as has been done in comparable and relevant research in the colorectal cancer screening field. 36 There is need to bring together experts (academic, public, patient, healthcare professional) in cancer screening harms, emotional processing, and scale measurement methodology to reach agreement on what to measure (outcomes) and how to measure it (outcome measures). 31 Existing relevant psychological theories could be utilised, such as those related to emotional response and processing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While appropriate guidelines were used to inform the specific psychometric properties by which outcome questionnaire measures were characterised, we did not undertake an assessment of the methodological quality of questionnaires, as is advocated by COSMIN. Future research could perform a more rigorous examination of the quality of questionnaire measures identified by the present review through application of the COSMIN Risk of Bias tool, as has been done in comparable and relevant research in the colorectal cancer screening field 36 …”
Section: Discussionmentioning
confidence: 99%
“…The COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) risk of bias checklist was developed to evaluate the quality of Patient-Reported Outcome Measures (PROMs) in systematic reviews [ 19 ]. A systematic review assessing quality of PROMs in the evaluation of psychosocial consequences in colorectal cancer reported that 90% of PROMs lacked content validity according to the COSMIN checklist [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal Cancer Screening (CRCS) can, like any other screening program, cause unintended harm, including physical and psychosocial harm [ 1 , 2 ]. Evidence has shown that the categorization of the unintended harms of CRCS lacks consensus [ 3 ]. However, there is an agreement that the most serious type of harm in CRCS is physical harms [ 2 ].…”
Section: Introductionmentioning
confidence: 99%